Effects of apelin-13 in mice model of experimental pain and peripheral nociceptive signaling in rat sensory neurons. (3rd May 2016) - Canpolat, Sinan; Ozcan, Mete; Saral, Sinan; Kalkan, Omer Faruk; Ayar, Ahmet
Abstract: Objective : Apelin-13 is an endogenous peptide with potential analgesic action, although the sites of its analgesic effects remain uncertain and the results are even controversial with regard to its pain modulating action. This study evaluated the possible pain-modulating action of peripherally administered apelin-13 using heat-induced, withdrawal latency to the thermal stimuli, acute pain model in mice. Involvement of peripheral mechanisms was tested, by using the intracellular calcium concentrations as a key signal for nociceptive transmission, in cultured rat dorsal root ganglion (DRG) neurons. Methods : DRG neurons were cultured on glass coverslips following enzymatic digestion and mechanical agitation, and loaded with the calcium-sensitive dye Fura-2 acetoxymethyl ester (1 µM). Intracellular calcium responses in individual DRG neurons were quantified by ratiometric calcium imaging technique. Results : Peripheral injection of a single dose of apelin-13 (100 mg/kg and 300 mg/kg) significantly decreases the latency to painful stimuli in a dose and time-dependent manner ( p  < 0.01, p  < 0.05, respectively, n  = 8 each). Apelin-13 (0.1 µM and 1 µM) did not produce a significant effect on cytoplasmic Ca 2+ ([Ca 2+ ]i ) responses, evoked by membrane depolarization, in cultured rat DRG neurons. Conclusion : Together these results indicate that apelin-13 can cause increased pain sensitivity after peripheral administration, but this effect does not involve calcium mediated signaling in primary sensory neurons.